Impact of climate change on infectious disease transmission: a CiteSpace- and VOSviewer- based visualization of enteric, respiratory and vector-borne infectious disease studies - Zhang, Tong; Liu, Jun (Frontiers in Climate, 2025)
ObjectiveThis study aims to address the research gaps in understanding the connections between climate change and infectious diseases by integrating bibliometric analysis with epidemiological perspectives and systematically identifying research trends and thematic evolution in this field.MethodsWe conducted a comprehensive bibliometric analysis of literature published between January 2010 and April 2025, retrieved from Web of Science, PubMed, CNKI, and Wanfang databases. Analytical methods included keyword co-occurrence mapping and cluster analysis using CiteSpace and VOSviewer.ResultsThe analysis revealed a steady increase in publication output, accompanied by a notable shift from single-disease studies to complex system assessments. Research patterns showed distinct thematic priorities: vector-borne diseases demonstrated significant growth after 2018; respiratory infections maintained consistent research attention, while enteric diseases received comparatively limited focus. These patterns reflect underlying socioeconomic disparities and regional climatic influences.ConclusionThis study underscores the need for more systematic research on the intersection of climate change and infectious diseases. Future work should develop multi-disease analytical frameworks, advance interdisciplinary methods integrating environmental and data sciences with public health, and strengthen global research networks by improving geographic coverage and data standardization. These efforts will enhance predictive capabilities and intervention strategies against climate-sensitive infectious diseases.